ANALISIS SEMIOTIKA PERUBAHAN LOGO BARU BANK MANDIRI - Nasrullah Nasrullah; Sifa Fauziah (Jurnal Komunikasi dan Bisnis, 2021)
This research discusses the meaning of the new logo of Bank Mandiri which encompasses several messages to layers of audience. This research conducted to find out the meaning contained in the new Bank Mandiri logo in communicating their service to public or customer through the font and color using on their revamped identity. Data analysis derived from signs such as colours, letters or words to attract the attention of researchers in search for the meaning. The method used in this research is a qualitative method using Saussure semiotics analysis. The result of this research demonstrated that the logo acts a pivotal role in building identity and construct their corporate image, which their new logo represents friendliness, humility, wealth, prosperity, trust, integrity and professionalism. In the end, Bank Mandiri has been successfully transformed themselves as new benchmark in Indonesian retail banking through spirit reinforced in their new identity